The Influence of Service Quality on Costumer Satisfaction in Regional Drinking Water Companies (PDAM) in Polewali Mandar District - Nurfadila, Nurfadila; S, Muh Rizal; Bakhtiar, Bakhtiar; Mardatilla, Andi Mahdiana (Jurnal Administrasi Bisnis, 2025)
The Influenca of Service Quality on Customers at the Regional Drinking Water Company (PDAM) Polewali Mandar Regency. Thesis. Business Administration Study Program, Faculty of Social Sciences and Law, Makassar State University, Supervised by Muh. Rizal S and Bakhtiar. This study aims to determine how much influence service quality has on customer satisfaction at the Regional Water Company (PDAM) Polewali Mandar Regency. This study uses quantitative research methods. The data collection technique used is through observation and questionnaires. The sample used in this study were 100 respondents in Polewali Mandar Regency. The data obtained from the research results were processed using data analysis and using the SPSS 22 application consisting of validity and reliability tests, descriptive statistical analysis techniques, simple linear regression analysis, and coefficient of determination. The results showed that the indicators used in each of these variables indicate the quality of service is in the good enough category, for indicators on the customer satisfaction variable are in the good category. Based on simple linear regression analysis, there is a significant influence between service quality and customer satisfaction at PDAM Polewali Mandar.